PENERAPAN MODEL PEMBELAJARAN INQUIRY LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI GAYA DISEKITAR KITA - Nurul Ilma; Munirah; Dewi Darmiyani Napu (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine whether the learning outcomes of science can be improved through the Inquiry learning model in fourth-grade students of SDN 4 Limboto. The method used in this study is the classroom action research (CAR) method. This research was conducted at SDN 4 Limboto in fourth-grade students. The object of this study is the application of the think pair share learning method in improving the learning outcomes of science students on the material of forces around us in fourth-grade SDN 4 Limboto. The subjects of this study were fourth-grade students of SDN 4 Limboto. Data collection techniques in this study were observation and tests. Based on the data analysis and learning process in the previous chapter, the researcher can conclude that learning using the inquiry learning model can improve the quality of science lessons on the material of forces around us in fourth-grade SDN 4 Limboto. Student learning outcomes before the application of the inquiry learning model had not reached the KKTP. After the application of the inquiry learning model, student learning outcomes increased, as can be seen in the increase in completeness in the pre-cycle from 35%, increasing in cycle 1 to 55%, and in cycle II increasing to 80%. Thus, student learning outcomes and analysis of observation sheets improved in a better direction with the application of the inquiry learning model.